Imaging Protocol, Feasibility, and Reproducibility of Cardiovascular Phenotyping in a Large Tri-Ethnic Population-Based Study of Older People: The Southall and Brent Revisited (SABRE) Study - Al Saikhan, Lamia; Alobaida, Muath; Bhuva, Anish; Chaturvedi, Nish; Heasman, John; Hughes, Alun D.; Jones, Siana; Eastwood, Sophie; Manisty, Charlotte; March, Katherine; Ghosh, Arjun K.; Mayet, Jamil; et al. (Frontiers in Cardiovascular Medicine, 2020)
Background: People of South Asian and African Caribbean ethnicities living in UK have a high risk of cardiometabolic disease. Limited data exist regarding detailed cardiometabolic phenotyping in this population. Methods enabling this are widely available, but the practical aspects of undertaking such studies in large and diverse samples are seldom reported. Methods: The Southall and Brent Revisited (SABRE) study is the UK’s largest tri-ethnic longitudinal cohort. Over 1400 surviving participants (58-85 y) attended the 2nd study-visit (2008-2011) during which comprehensive cardiovascular phenotyping, including 3D-echocardiography (3D-speckle-tracking (3D-STE)), computed tomography, coronary artery calcium scoring, pulse-wave velocity, central blood pressure, carotid artery ultrasound and retinal imaging were performed. We describe the methods used with the aim of providing a guide to their feasibility and reproducibility in a large tri-ethnic population-based study of older people. Results: Conventional echocardiography and all vascular measurements showed high feasibility (>90% analyzable of clinic-attendees). 3DE and 3D-STE were less feasible in this age group (76% 3DE acquisition feasibility and 38% 3D-STE feasibility of clinic-attendees). Intra- and inter-observer variabilities were excellent for most of conventional and advanced echocardiographic measures. The test-retest reproducibility was good-excellent and fair-good for conventional and advanced echocardiographic measures, respectively, but lower than when re-reading the same images. All vascular measures demonstrated excellent or fair-good reproducibility. Conclusions: Detailed cardiovascular phenotyping is feasible and reproducible in an ethnically diverse population. The data collected will lead to a better understanding of why people of South Asian and African Caribbean ancestry are at elevated risk of cardiometabolic diseases.